AN ANALYSIS OF PRONUNCIATION ERRORS IN ENGLISH AMONG KELANTANESE MALAY STUDENTS - NUR DIANA, KAMARUL ZAMAN (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study aims to describe the phonological features of Kelantanese Malay students’ pronunciation in English according to Contrastive Analysis (CA) and Error Analysis (EA) with the prediction that these errors are neither coincidental nor randomly made and to see the similarities and differences between the Kelantanese students’ pronunciation and receive pronunciation are analysed together with the type of pronunciation errors made by the students, and the formulation of phonological rules. In order to test subjects’ pronunciation, speech samples involving words and a short passage were recorded . Data were collected and analysed based on phonemic transcriptions in the Cambridge English Pronouncing Dictionary. By using Contrastive Analysis, the sound systems of English and Kelantan dialect were compared to see the potential difficulties of English pronunciation among twenty Kelantanese Malay subjects who are secondary school students who are at the age of seventeen. Apart from that, based on Error Analysis, the pronunciation errors of subjects were further classified into seven categories which were substitution, deletion, insertion, glottalization, monophthongization and vowel lengthening. The results of the study show the areas of difficulty on the pronunciation of particular phonemes for the Kelantanese students. The findings help to provide a clear understanding of the common characteristics of pronunciation errors made by the Kelantanese students.